Effects of Different Drip Irrigation Patterns on Grain Yield and Population Structure of Different Water- and Fertilizer-Demanding Wheat (Triticum aestivum L.) Varieties - Jianguo Jing; Zhaofeng Li; Fu Qian; Xinyi Chang; Weihua Li (Agronomy, 2023)
A suitable population structure is the foundation for a high yield of wheat. Studying the changes in yield and population structure of different wheat rows under drip irrigation conditions can provide a theoretical basis for optimizing wheat drip irrigation pattern. In a two-year field experiment, two different water- and fertilizer-demanding spring wheat varieties (XC22 and XC44) were used to study the changes of stem and tiller dynamics, dry matter accumulation, canopy photo-synthetically active radiation (PAR) interception, and canopy apparent photosynthesis rate (CAP) under one tube serving four rows of wheat drip irrigation pattern (TR4, drip lateral spacing (DLS) = 60 cm, wheat row spacing (WRS) = 15 cm) and one tube serving six rows of wheat drip irrigation pattern (TR6, DLS = 90 cm, WRS = 15 cm; TR6L, DLS = 90 cm, WRS = 10 cm and TR6S, DLS = 80 cm, WRS = 10 cm). The results showed that under the condition of equal row spacing of 15 cm, after increasing the number of wheat rows serving by one drip irrigation tube from four (TR4, control) to six (TR6), the yields (water use efficiency) of XC22 and XC44 were lower by 11.19% and 8.63%, respectively. The reduction of yield was related to uneven population growth, specifically as follows: compared with the first wheat row (R1), at flowering stage the leaf area index (LAI) and PAR interception in the third wheat row (R3) of XC22 and XC44 were significantly decreased by 30.02%, 18.69%, 9.59%, and 14.74%, respectively. At the maturity stage, the biomass, plant height, and panicles number of tiller (TPN) in R3 were significantly decreased by 22.15%, 12.34%, 15.46%, 5.24%, 65.07%, and 42.11%, respectively. At the jointing, flowering, and milk-ripening stage, the CAP were significantly decreased by 24.65%, 22.85%, 17.06%, 14.02%, 42.14%, and 32.27%, respectively, the decrease of XC22 were all higher than that of XC44 (except for PAR interception). After the TR6 pattern was processed to narrow the wheat row spacing from 15 cm to 10 cm under the condition of the same drip tube lateral spacing (TR6L) and under the condition of shortening drip tube lateral spacing by 10 cm (TR6S), the yields in R3 of XC22 and XC44 were significantly increased by 20.07%, 18.43%, 30.39%, and 23.80%, respectively, and the increase in yields were related to the improvement of LAI, biomass, plant height, TPN, PAR interception, and increased population photosynthesis. Among the four drip irrigation patterns, for both XC22 and XC44, the yield of TR6S was the closest to that of TR4, and the yields of them were significantly higher than that of TR6 and TR6L.